Vaccination status among COVID-19 patients and duration of Polymerase Chain Reaction test positivity: evaluation of immunization schedule and type of vaccine - Guerriero, Paola; Cipollone, Claudia; Martinelli, Roberta; Caputo, Federica; Cervellini, Maurizio; Mammarella, Leondino; Muselli, Mario; Mastrantonio, Riccardo; Mastrangeli, Giada; Fabiani, Leila (Annali di Igiene Medicina Preventiva e di Comunità, 2024)
Background. The introduction of the vaccine against SARS-CoV-2 has represented a cornerstone in the containment of the pandemic. Our aim was to assess the vaccination schedules in relation to the infection free interval and to the duration of positivity in case of infection. Study design. This study involves the SARS-CoV-2 infected people managed by the Local Health Authority ASL 1 Abruzzo. The data collected included: vaccine administration date, vaccine type, information on the Polymerase Chain Reaction test positivity, and demographic variables, such as age and sex. Methods. The duration of Polymerase Chain Reaction test positivity was assessed in relation to the vaccination status, the vaccine type and the time interval between the last vaccination dose and the first nasopharyngeal positive swab over the considered period. Results. The infection duration (DAYS) was significantly shorter in subjects vaccinated with a booster dose than unvaccinated subjects (12.8 vs 14.6; p<0.0001) and subjects vaccinated with the primary series only (12.8 vs 14.1; p<0.0001). Duration of PCR positivity was shorter with heterologous immunisation than with other vaccination schedules (p=0.0317). Conclusions. This study highlights, in a large cohort of patients, the association between vaccination schedule and the response to infection.